Mapping the Causes of Neonatal Deaths in Indonesia: Insights from AMPSR Neonatal Assessments - Sulicha Nurhayati; Martha Irene Kartasurya; Cahya Tri Purnami (Universitas Malahayati, 2026)
ABSTRACT Neonatal mortality remains a significant public health concern in Indonesia, with preventable causes persisting despite ongoing health interventions. This study aimed to map the causes and contributing factors of neonatal deaths in Indonesia using Maternal and Perinatal Audit and Surveillance Response (AMPSR) assesment. A scoping review method was employed, systematically searching three major databases for relevant articles published between 2021 and 2025. Twenty articles met the inclusion criteria and were analyzed narratively. The findings reveal that the leading direct causes of neonatal deaths include prematurity and its complications, birth asphyxia, neonatal infections, congenital anomalies, and neonatal tetanus. Indirect factors, such as maternal health conditions, inadequate antenatal care, health system limitations, and sociodemographic disparities, further exacerbate neonatal mortality risks. The results underscore the importance of integrated strategies that strengthen maternal and neonatal health services, improve care quality and access, and address broader social determinants. This study provides comprehensive evidence to inform policy and intervention priorities aimed at reducing neonatal deaths in Indonesia. Keywords: Neonatal Mortality, AMPSR, Indonesia, Causes of Death, Maternal Health.